Pollen morphology of Astragalus L. sect. Onobrychoidei DC. (Fabaceae) in Turkey - Pinar, Nur M.; Ekici, Murat; Aytac, Zeki; Akan, Hasan; Ceter, Talip; Alan, Senol (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2009)
The pollen morphology of 45 specimens of 29 species of the genus Astragalus L. of the section Onobrychoidei DC. distributed in Turkey was Studied with light and electron microscopies. The pollen is generally 3-colporate. Pollen of the section is prolate, subprolate, and prolate-spheroidal. Size varies, with the polar axis ranging from 23.4 to 42.6 mu m and the equatorial axis from 14.3 to 36.4 mu m. The Outline is elliptic or compressed oval in the meridional section, versus trilobulate and sometimes tetralobulate in the polar optical section. Sculpturing is usually microreticulate, rarely reticulate or rugulate in the meridional optical section, and psilate and perforate (with irregular or circular perforations) in the polar optical section.
Keywords: health sciences; medical and health sciences; basic medicine; polen,morfoloji